2019
DOI: 10.11604/pamj.2019.33.127.18101
|View full text |Cite
|
Sign up to set email alerts
|

Association entre le paludisme et le faible poids de naissance à Yaoundé, Cameroun

Abstract: IntroductionLe faible poids de naissance (FPN) est un important prédicteur de survie de l’enfant et de son développement ultérieur. De par sa physiopathologie, le paludisme est présumé en être un des facteurs de risques. La présente étude avait pour but de déterminer l’association entre l’accès palustre chez la femme enceinte (FE) et la survenue du FPN (poids < 2500 g).MéthodesIl s’est agi d’une enquête analytique de type cas-témoins, basée sur l’administration d’un questionnaire et d’une grille d’observation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
2
1
0
Order By: Relevance
“…Open Journal of Epidemiology At least one in ten children in our study had LBW. Similar results were reported in Cameroon in 2019 [28], Burkina Faso in 2020 [18], and Benin in 2017 [26], where the authors had reported a LBW prevalence of 12.3%, 11.0%, and 10.9%, respectively. A higher prevalence was observed in Niger where it was estimated at 38.4% in 2020 [6].…”
Section: Discussionsupporting
confidence: 85%
“…Open Journal of Epidemiology At least one in ten children in our study had LBW. Similar results were reported in Cameroon in 2019 [28], Burkina Faso in 2020 [18], and Benin in 2017 [26], where the authors had reported a LBW prevalence of 12.3%, 11.0%, and 10.9%, respectively. A higher prevalence was observed in Niger where it was estimated at 38.4% in 2020 [6].…”
Section: Discussionsupporting
confidence: 85%
“…At least one in ten children had Low Birth Weight (LBW) in our study. Similar results were reported in Cameroon in 2019 [21], Burkina Faso in 2020 [19], and Benin in 2017 [20], where the authors had reported a LBW prevalence of 12.3%; 11.0% and 10.9%, respectively. Higher prevalence was observed in Niger in 2020 where it was estimated at 38.4% in 2020 [6].…”
Section: Discussionsupporting
confidence: 82%
“…In almost all studies, the most frequently reported associated factors to pregnancy malaria were early pregnancy age, primigravidae, not sleeping under insecticide treated bednet and insufficient IPT-sp [23,26,28,29]. According to a hospitalbased study in an urban area of Cameroon where pregnancy malaria was a risk factor of low birth weight, taking at least three doses of IPT-sp was associated to reduced risk of low birthweight [30].…”
Section: Introductionmentioning
confidence: 99%